Stability and antimicrobial effect of amikacin-loaded solid lipid nanoparticles - Solmaz Ghaffari (Dove Medical Press, 2010)
Solmaz Ghaffari1, Jaleh Varshosaz1, Afrooz Saadat2, Fatemeh Atyabi21Department of Pharmaceutics, Faculty of Pharmacy and Isfahan Pharmaceutical Sciences Research Center, Isfahan University of Medical Sciences, Isfahan, Iran; 2Department of Pharmaceutics, Faculty of Pharmacy, Tehran University of Medical Sciences, Tehran, IranAbstract: Solid lipid nanoparticles (SLNs) of amikacin were designed in this study for pulmonary delivery to reduce the dose or its administration intervals leading to reduction of its toxicities especially in long term treatment. Nanoparticles of amikacin were prepared from cholesterol by solvent diffusion technique and homogenization. The size, zeta potential, loading efficiency, and release profile of the nanoparticles were studied. The conventional broth macrodilution tube method was used to determine the minimum inhibitory concentration (MIC) and minimum bacteriostatic concentration (MBC) of amikacin SLNs with respect to Pseudomonas aeruginosa in vitro. To guarantee the stability of desired SLNs, they were lyophilized using cryoprotectants. Results showed that considering the release profile of amikacin from the studied nanocarrier, MIC and MBC of amikacin could be about two times less in SLNs of amikacin compared to the free drug. Therefore, fewer doses of amikacin in SLNs can clear the infection with less adverse effects and more safety. Particle size enlargement after lyophilization of desired SLNs after two months storage was limited in comparison with non-lyophilized particles, 996 and 194 nm, respectively. Zeta potential of lyophilized particles was increased to +17 mV from +4 mV before lyophilization. Storage of particles in higher temperature caused accelerated drug release.Keywords: amikacin, antimicrobial effects, Pseudomonas aeruginosa, solid lipid nanoparticles, stability